Auspicious time Verse to Culture and Society of Lao Ethnic group in Pha-O Village, Luang Prabang city, Luang Prabang province - keoboukhong, bounthavy (Souphanouvong University Journal Multidisciplinary Research and Development, 2025)
This article aims to classify and analyze the content of the Lao people in Ban Pha-O, Prabang Capital, Luang Prabang Province. The research design employed a qualitative study approach, which involved interviews, reading, observation, analysis, and classification. The collection of 10 people's lamentations resulted in a total of 27 lamentations, and the research tool used was an interview question. The results can be summarized as follows: The result found that there were 6 main types: lamentations about choosing a spouse; lamentations about vehicles, lamentations about equipment, lamentations about building a house, lamentations about plants, and lamentations about clothing. In particular, in terms of the content of the lamentations about cutting down trees to build a house or building a house; Contents of the poem "Kham Sok Van Kwa" (Worship of the Day of Planting Plants); Contents of the poem "Kham Sok Kong" (Worship of the Day of Planting Plants); Contents of the poem "Kham Sok Kae".